SURVEY OF PLANT PARASITIC NEMATODES ON POTATOES IN DALAT - Lê Thị Ngọc; Trần Trung Kiên; Nguyễn Ngọc Kiều Oanh; Hoàng Thị Thu Thảo; Lê Bá Lê; Hồ Thị Thu Hòa; Trần Thị Minh Loan (Tạp chí Khoa học Đại học Đà Lạt)
Plant-parasitic nematodes on potato were identified by morphology of juveniles and adults. Extraction of vermiform nematodes in soil and roots was made by modified Baermann technique and root gall index was dertermined following Bridge and Page (1980) chart. Results show that there were six genus, five families and one order of parasitic-plant nematodes in soil. The ratio of Helicotylenchus was the highest (93.33%), followed by Meloidogyne (83.33%), Pratylenchus (50%), Criconemella (33.33%), Ditylenchus (30%), and Globodera at only 20%. Density of plant parasitic nematodes ranged from 500 individuals to 3,000 individuals per 50 cm3 of soil, 200 to 2,204 individuals per 5 grams of roots. Root gall index ranged from 1,754 to 5,262.